Discovery of 3, 6-diaryl-1H-pyrazolo[3, 4-b]pyridines as potent anaplastic lymphoma kinase (ALK) inhibitors. Issue 7 (1st April 2019) - Chen, Changwei; Pan, Peichen; Deng, Ziyang; Wang, Dahai; Wu, Qifan; Xu, Lei; Hou, Tingjun; Cui, Sunliang
Graphical abstract: Abstract: A new series of 3, 6-diaryl-1 H -pyrazolo[3, 4- b ]pyridine compounds have been discovered as potent anaplastic lymphoma kinase (ALK) inhibitors. The 4-hydroxyphenyl in the 6-position of 1 H -pyrazolo[3, 4- b ]pyridine were crucial and a fluorine atom substitution could give promising inhibitory activity. The IC50 of compound9v against ALK was up to 1.58 nM and a binding mechanism was proposed.